2014
DOI: 10.1007/s00216-014-7742-7
|View full text |Cite
|
Sign up to set email alerts
|

Biological and chemical investigation of Allium cepa L. response to selenium inorganic compounds

Abstract: The aim of this study was to evaluate the biological and chemical response of Allium cepa L. exposed to inorganic selenium compounds. Besides the investigation of the total content of selenium as well as its chemical speciation, the Allium test was used to evaluate the growth of onion roots and mitotic activity in the roots’ meristem. The total content of selenium was determined by inductively coupled plasma mass spectrometry (ICP MS). High-performance liquid chromatography (HPLC), coupled to ICP MS, was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 8 publications
(13 reference statements)
2
17
0
Order By: Relevance
“…According to the International Union of Pure and Applied Chemistry (IUPAC) statement [32], selection of a suitable extraction method for individual compounds is one of the most difficult tasks in speciation analysis, mainly due to their very low concentration and presence in complex matrices. The extraction procedures of selenium species from biological samples involve boiling in water [33][34][35], use of Tris-HCl buffer, acid hydrolysis [36] and enzymes such as protease [36], pronase [37], proteinase K [38], and protease-lipase [20]. Extraction is commonly supported by sonication or mechanical shaking of the sample with added inorganic and organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Union of Pure and Applied Chemistry (IUPAC) statement [32], selection of a suitable extraction method for individual compounds is one of the most difficult tasks in speciation analysis, mainly due to their very low concentration and presence in complex matrices. The extraction procedures of selenium species from biological samples involve boiling in water [33][34][35], use of Tris-HCl buffer, acid hydrolysis [36] and enzymes such as protease [36], pronase [37], proteinase K [38], and protease-lipase [20]. Extraction is commonly supported by sonication or mechanical shaking of the sample with added inorganic and organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Se, an essential trace element, is involved in various physiological processes within our bodies and protects against several diseases, including Alzheimer's disease, cardiovascular disease and cancer . Several studies have demonstrated that a number of daily foods and nutritional supplements, e.g., garlic, onion, yeast and chlorella extracts, contain large amounts of Se . In 1999, a study by Ganther demonstrated the biological activity of Se was provided by Se‐conjugate compounds, not the element itself .…”
Section: Introductionmentioning
confidence: 99%
“…Anion-exchange chromatography has been mainly employed in selenium speciation analysis [58][59][60][61][62][63]. Mobile phases used in this mode usually contain small content of organic modifier (e.g., 2-5% methanol) and buffered salt solution (e.g., acetate, phosphate, and citrate).…”
Section: Ion-exchange Chromatographymentioning
confidence: 99%